Empowering Local MSMEs through Regional Policies: A Focus on Featured Products in Barru Regency - Usamah Mahmud; Wahyul AZ (P3M Stia Al Gazali Barru and Meraja media, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal